Land‐use change and the ecological consequences of personality in small mammals. (17th June 2019) - Brehm, Allison M.; Mortelliti, Alessio; Maynard, George A.; Zydlewski, Joseph
Abstract: Many plants rely on animals for seed dispersal, but are all individuals equally effective at dispersing seeds? If not, then the loss of certain individual dispersers from populations could have cascade effects on ecosystems. Despite the importance of seed dispersal for forest ecosystems, variation among individual dispersers and whether land‐use change interferes with this process remains untested. Through a large‐scale field experiment conducted on small mammal seed dispersers, we show that an individual's personality affects its choice of seeds, as well as how distant and where seeds are cached. We also show that anthropogenic habitat modifications shift the distribution of personalities within a population, by increasing the proportion of bold, active, and anxious individuals and in‐turn affecting the potential survival and dispersal of seeds. We demonstrate that preserving diverse personality types within a population is critical for maintaining the key ecosystem function of seed dispersal.